Education Values In Novel Madogiwa No Totto-Chan By Tetsuko Kuroyanagi - Pandi, H M L (Journal of Educational Method and Technology, 2019)
This study aims to gain an in-depth understanding of educational values in the novel Madogiwa No Totto-chan by Tetsuko Kuroyanagi with a qualitative approach that includes educational values in terms of the structure of the novel. Research methods. This research is a library research or library research that uses a qualitative approach with content analysis techniques. Conclusion of research findings: The main theme of this novel is EDUCATION, education that frees students to be creative, while the sub-theme is education must be adjusted to the development of the child's personality. The credentials found are: A mother must be wise in educating and caring for her children with special needs. A school principal or a teacher should be a leader who is brave to act in accordance with their respective beliefs and life principles. The educational values in this novel can be used as examples of learning in schools to help children with problems (special needs). An educator should be fun and not scold his students because educating children is not with anger but with advice, praise, and trust. Make kids confident, responsible, love each other, and help each other, introduce them to nature because nature stores various sources of knowledge. Educational values found are educational values related to religious education values, moral education values, social education values, and beauty education values. Recommendation: Madogiwa No Totto-chan's autobiographical novel (Totto-chan Little Girl in the Window) can be used as a learning tool for character education in schools in Indonesia because this Japanese novel has raised educational values that contain a number of noble values. One of the noble values is the value of education in the novel that abstracts the reality of Japanese society's life. Education in Japan can be applied to education in Indonesia.Â Keywords: Novel; Educational Values